2018
DOI: 10.1016/j.apsb.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation treatment of primary lung cancer using liposomal curcumin dry powder inhalers

Abstract: Lung cancer is the leading cause of cancer-related deaths. Traditional chemotherapy causes serious toxicity due to the wide bodily distribution of these drugs. Curcumin is a potential anticancer agent but its low water solubility, poor bioavailability and rapid metabolism significantly limits clinical applications. Here we developed a liposomal curcumin dry powder inhaler (LCD) for inhalation treatment of primary lung cancer. LCDs were obtained from curcumin liposomes after freeze-drying. The LCDs had a mass m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(84 citation statements)
references
References 53 publications
(52 reference statements)
1
81
0
2
Order By: Relevance
“…Studies have shown that curcumin could suppress tumorigenesis, inhibit tumor promotion, and suppress angiogenesis (12). Curcumin could not only inhibit cell proliferation of tumor cells, but could also inhibit the proliferation of normal cells (13). For example, curcumin significantly inhibited the proliferation of BEAS-2B cells at the concentration of 10 μmol L -1 (14).…”
Section: Curcumin Inhibits Cell Proliferation In A549 Cellsmentioning
confidence: 99%
“…Studies have shown that curcumin could suppress tumorigenesis, inhibit tumor promotion, and suppress angiogenesis (12). Curcumin could not only inhibit cell proliferation of tumor cells, but could also inhibit the proliferation of normal cells (13). For example, curcumin significantly inhibited the proliferation of BEAS-2B cells at the concentration of 10 μmol L -1 (14).…”
Section: Curcumin Inhibits Cell Proliferation In A549 Cellsmentioning
confidence: 99%
“…Since ancient times it has been used along other curcuminoids extracted from turmeric in traditional medicine due to its beneficial influence on human health. Curcumin shows anti-oxidant ( 1 ), anti-inflammatory ( 2 ), anti-microbial ( 3 ) and anti-tumor ( 4 ), nephro-protective ( 5 ) and anti-diabetic ( 6 ) activities. Importantly, curcumin is safe even at high doses ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve curcumin dispersing in aqueous solutions and enhance its biological activity, many studies have been conducted on its formulations such as liposomes, nanoparticles, micelles, phospholipid complexes, hydrogels, powder solutions, solid dispersions and nanoemulsions . Topical administration of curcumin may be a fundamental solution to curcumin biomedical application because it remains local . Some topically curcumin formulations were applied for therapy of vaginal infection .…”
Section: Introductionmentioning
confidence: 99%